Electrical Indices of Rod Dysfunction - Lovasik, J.V.; Williams, T.D. (Canadian Journal of Optometry, 2021)
Patients presenting with night time vision difficulties and a family history of retinitis pigmentosa require special testing procedures even in the absence of typical functional deficits or ophthalmoscopically visible retinal disease. The authors discuss various theoretical aspects of electroretinography and their practical clinical applications in objectively identifying the physiological defect occurring in retinitis pigmentosa.